Upper mantle deformation signatures of craton-orogen interaction in the Carpathian-Pannonian region from SKS anisotropy analysis - Petrescu,L; Graham,S; Houseman,G; Bastow,I (Geophysical Journal International, 2020)
Since the Mesozoic, central and eastern European tectonics have been dominated by the closure of the Tethyan Ocean as the African and European plates collided. In the Miocene, the edge of the East European Craton and Moesian Platform were reworked in collision during the Carpathian orogeny and lithospheric extension formed the Pannonian Basin. To investigate the mantle deformation signatures associated with this complex collisional-extensional system, we carry out SKS splitting analysis at 123 broad-band seismic stations in the region. We compare our measurements with estimates of lithospheric thickness and recent seismic tomography models to test for correlation with mantle heterogeneities. Reviewing splitting delay times in light of xenolith measurements of anisotropy yields estimates of anisotropic layer thickness. Fast polarization directions are mostly NW–SE oriented across the seismically slow West Carpathians and Pannonian Basin and are independent of geological boundaries, absolute plate motion direction or an expected palaeo-slab roll-back path. Instead, they are systematically orthogonal to maximum stress directions, implying that the indenting Adria Plate, the leading deformational force in Central Europe, reset the upper-mantle mineral fabric in the past 5 Ma beneath the Pannonian Basin, overprinting the anisotropic signature of earlier tectonic events. Towards the east, fast polarization directions are perpendicular to steep gradients of lithospheric thickness and align along the edges of fast seismic anomalies beneath the Precambrian-aged Moesian Platform in the South Carpathians and the East European Craton, supporting the idea that craton roots exert a strong influence on the surrounding mantle flow. Within the Moesian Platform, SKS measurements become more variable with Fresnel zone arguments indicating a shallow fossil lithospheric source of anisotropy likely caused by older tectonic deformation frozen in the Precambrian. In the Southe